2015
DOI: 10.1155/2015/913843
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Studies of Postpartum Depression: An Overview

Abstract: Postpartum depression is a frequent and disabling condition whose pathophysiology is still unclear. In recent years, the study of the neural correlates of mental disorders has been increasingly approached using magnetic resonance techniques. In this review we synthesize the results from studies on postpartum depression in the context of structural, functional, and spectroscopic magnetic resonance studies of major depression as a whole. Compared to the relative wealth of data available for major depression, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…PPD and MDD, assessed independently, show an amygdalar hypo‐responsiveness and hyper‐responsiveness, respectively, to negative stimuli. In addition, it is difficult to compare and interpret the neuroimaging literature on the neural responsiveness to infant stimuli as a result of the wide variability in methodologies such as stimulus modality (auditory, visual), standardisation of the stimuli, sample size, analysis methods and the postpartum stage of mothers …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPD and MDD, assessed independently, show an amygdalar hypo‐responsiveness and hyper‐responsiveness, respectively, to negative stimuli. In addition, it is difficult to compare and interpret the neuroimaging literature on the neural responsiveness to infant stimuli as a result of the wide variability in methodologies such as stimulus modality (auditory, visual), standardisation of the stimuli, sample size, analysis methods and the postpartum stage of mothers …”
Section: Discussionmentioning
confidence: 99%
“…What we do know about the neural underpinning of the condition/disorder is a result of a few recent functional magnetic resonance imaging (fMRI) studies. 17,42 These studies have identified an inverse relationship between amygdala responsiveness to negative stimuli (including infant faces in distress) and symptom severity in PPD. 43,44 Thus, in comparison to non-depressed mothers, depressed mothers show reduced amygdalar responses to negative infant-related stimuli.…”
Section: Depression Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal coherence of the BOLD signal is then compared to the timing of the task to extract the location of voxels that are active during the performance of the task. fMRI has been used extensively to study motor, sensory, and language activation and is clinically used as a complementary imaging technique in neuropsychiatric and neurodegenerative diseases such as schizophrenia [34], attention deficit and hyperactivity syndrome [35], and depression [36]. It may also be used to determine hemispheric language dominance in the pre-operative setting (e.g., before temporal lobectomy or hemispherectomy in patients with medically refractory epilepsy) or for surgical planning in the setting of brain masses [37].…”
Section: Current Applications For Bold Mrimentioning
confidence: 99%
“…Some authors have emphasized the role of oxytocin [148,150]. In the last 5 years, neuroscientists have begun to examine differences in ‘the parental brain' when the mother is depressed [147,149,151,152,153,154,155], but there has so far been no attempt to study rejecting mothers. …”
Section: Diagnosis and Measurementmentioning
confidence: 99%